Facile Preparation of Activated Carbon/Zinc Oxide Nanocomposite for Supercapacitor Application - Talalah Ramli, Nurul I.; Rafaie, Hartini Ahmad; Kasim, Muhd Firdaus; Ibno, Hanifa Binti (Recent Innovations in Chemical Engineering, 2020)
Objective: An efficient and facile preparation route has been developed to prepare activated carbon (AC)/zinc oxide (ZnO) nanocomposite electrodes for the supercapacitor electrode. Methods: The zinc oxide nanostructure was synthesized via the sol-gel method by using conventional hexamethylenetetramine (HMTA) reagent as the reducing agent. Results: The physicochemical and electrochemical properties of the nanocomposites were characterized by X-ray diffraction analysis (XRD) and cyclic voltammetry (CV) analysis, respectively. 10 wt% of ZnO loading shows an optimum specific capacitance of 398 F/g at a scan rate of 50 mV/s. The optimum sample retained 96% of its initial specific capacitance upon 100 consecutive cycles. Conclusion: The enhanced specific capacitance can be ascribed to the synergistic effect of the individual properties of AC and ZnO.
Keywords: X-ray